The theme of the homeland in Tuvan and Buryat prose of the 1960s–1970s - Imikhelova, Svetlana S.; Mongush, Evgeny D.; Sinyachkin, Vladimir P. (The New Research of Tuva, 2024)
The article conducts a comparative analysis of Tuvan and Buryat prose from the 1960s — 1970s dedicated to the theme of homeland and native land. The depiction of the home and associated motifs of memory, childhood, as well as the images of the native nature are highlighted as reflections of ethnocultural values and points of intersection between the two literary traditions. The artistic explorations of Tuvan and Buryat writers in autobiographical prose are examined, revealing both similarities in the convergence of specific-domestic and universal-being spheres, and differences stemming from genre choices and narrative techniques. In Tuvan autobiographical works on the theme of homeland, an original fusion of prose and poetry is analyzed, leading to the genre profile of a lyrical epic. Buryat prose explores narrative traditions of the historical novel using the structure of text within text and autobiographical books with a reliance on journalistic pathos. The conclusion is drawn regarding the endeavor of Tuvan and Buryat writers to elevate the theme of homeland to the level of universal cultural experience. This allows emphasizing the common and distinctive elements in the discovery of new genre modifications, changes in narrative structure, the portrayal of the narrator-hero, and their relationships with the author and reader.